2004
DOI: 10.1023/b:itde.0000026475.55323.01
|View full text |Cite
|
Sign up to set email alerts
|

DEPTH – Developing Professional Thinking for Technology Teachers: An International Study

Abstract: The tools to help teachers reflect on their professional knowledge are few in number, and often difficult to utilise. This paper reports on a study conducted with both primary and secondary technology initial teacher education students in a number of different countries who were given the same teacher-knowledge graphical framework as a tool to support reflection on their own professional knowledge. We wanted to investigate if, despite the different country contexts, student teachers of technology could take ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…From a pedagogical perspective, D&T is said to be characterised by a pedagogy where there is no 'right answer' but rather different responses to the same problem are valued, some more than others (Banks et al 2004). Spendlove (2012) highlighted that working in a space bereft of explicitly defined content knowledge as a unique advantage of D&T education, in that ownership lies with the teacher, who can in turn draw upon their own interests, their students' interests, and recent developments in the field to engage learners with relevant concepts when required.…”
Section: The Nature Of Dandt Educationmentioning
confidence: 99%
“…From a pedagogical perspective, D&T is said to be characterised by a pedagogy where there is no 'right answer' but rather different responses to the same problem are valued, some more than others (Banks et al 2004). Spendlove (2012) highlighted that working in a space bereft of explicitly defined content knowledge as a unique advantage of D&T education, in that ownership lies with the teacher, who can in turn draw upon their own interests, their students' interests, and recent developments in the field to engage learners with relevant concepts when required.…”
Section: The Nature Of Dandt Educationmentioning
confidence: 99%
“…Much has been written about the importance of reflective practice for professional development (cf Wood et al 2009;Race 2007;McCormack 1997;Schön 1991;Luft 1982) and specifically for teachers (cf Banks et al 2004;Jay and Johnson 2002;Brookfield 1995). Ericsson and Pool (2016) write about naïve, purposeful and deliberate practice.…”
Section: Central Concepts and Literature Reviewmentioning
confidence: 99%
“…The study of a professional development experience for teachers, reported in this paper, was underpinned by the model shown in Fig. 1, which is an integration of the models of Banks et al (2004) and Stein et al (2000). By combining the two models (Banks et al, 2004;Stein et al, 2000), we attempted to devise a clearer, simpler model than the original model (Stein et al, 2000) that would underpin and guide our interactions with teachers, as well as form a framework for data collection and analysis during the study.…”
Section: Introductionmentioning
confidence: 97%
“…Alongside this, the need for teachers to develop sophisticated notions of the role knowledge plays in society, and to be able to create futures-oriented and equitable learning environments responsive to students needs, have become paramount (Education Queensland, 2000). Banks and Barlex's (1999) teacher education experience, and the professional development studies undertaken by Banks et al (2004), and Jones and Moreland (2004) have highlighted the changes and challenges to teacher professional knowledges (Shulman, 1986) when technology education is introduced. For example, there has been recognition of the important place teachers' personal subject construct knowledge has in underpinning the whole range of their professional knowledge about technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation